Potential development of Irish agricultural sustainability indicators for current and future policy evaluation needs - Lynch, J; Donnellan, T; Finn, J; Dillon, E; Ryan, M (Elsevier, 2018)
There is a significant and detailed range of sustainability indicators for Irish agri-food production, but there remain areas where further indicator development or new indicators could prove valuable. This review provides an outline of potential developments in Irish assessment of agricultural sustainability following the latest research and in order to meet policy demands. Recent research findings have suggested means of improved quantitative modelling of greenhouse gas emissions, but additional dietary and soil data may be important for this, especially for the potential inclusion of any soil sequestration. This information could also benefit more detailed modelling of nutrient losses to water. Specific concerns over pesticide and antibiotic use may require additional survey work on the particular locations or types of farms of interest. Biodiversity monitoring could be improved by expanding the range of results-oriented agri-environment schemes or employing remote-sensing habitat monitoring, likely supplemented with targeted field surveys for specific objectives. Farm-level economic sustainability is largely well-covered, but additional data collection may be of benefit to address specific issues such as labour costs. Recent additional surveys on farm-level social sustainability have addressed important social indicators of isolation and access to local services, and could be rolled out on a larger number of farms in the future. Wider societal concerns such as animal welfare, genetically modified materials in foodstuffs and antibiotic resistance have limited indicators currently available, and could also benefit from additional surveys. The breadth and detail required in agri-food sustainability indicators present a significant challenge to survey design and implementation, but many developments can be achieved without additional surveys through the use of remote sensing and geospatial technologies and integration of existing datasets. Despite the important benefits of further developments in Irish sustainability indicators, consideration must also be given to farmer confidentiality and survey fatigue.